Molecular cloning of a mouse submaxillary gland renin cDNA fragment. - Rougeon, F (1981)
The mRNA encoding mouse renin has been partially purified from total poly(A)-containing RNA of submaxillary glands of male Swiss mice. Corresponding cDNAs were cloned in the Pst I site of pBR322. Recombinants have been characterized by differential screening and hybrid-arrested translation. The DNA of clone pRn3-5 has been used to study the expression of renin mRNA in the submaxillary gland and in the kidney of different mouse strains. The renin mRNA from submaxillary gland and kidney have the same length (1600 nucleotides) and appear to be the products of the same gene. In vitro translation of mRNAs and RNA blotting experiments have shown that renin mRNA sequences are accumulated in the submaxillary gland of males of AKR and Swiss strains but not in the gland of male BALB/c.